Faktor Yang Mempengaruhi Wanita Usia Subur Dalam Melakukan Tes Inspeksi Visual Asam Asetat (IVA) - Nurjanah, Suci; Asriwati, Asriwati; Sibero, Jitasari Tarigan (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Cervical cancer is the second most found cancer in women in the world. About 500,000 new cases of cervical cancer occur each year and three-quarters occur in developing countries. However, this cervical cancer can often still be cured if found early with the method of Visual Acetate Acid Inspection (IVA). The scope of implementation of Sapat Health Center IVA in 2019 for women of childbearing age aged 30-50 is 20.95%. The purpose of this study was to determine the factors that influence women of childbearing age in conducting the Acetic Acid Visual Inspection test. This type of research is quantitative with cross sectional approach. The population is all women of childbearing age aged 30-50 years as many as 3240 people. The sample of this research is 97 respondents with Proposional Random Sampling technique. Data analysis used univariate, bivariate (Chi Square test), and multivariate analysis (multiple logistic regression tests). The results showed that factors influencing women of childbearing age in conducting IVA were attitudes p value 0.001, cadre support p value 0.021, and sources of information p value 0.036. While the factors that have no effect are knowledge, husband's support, and perception. The most dominant factor influencing was cadre support with an OR value of 14,144 (95% CI = 1501-133,286). The conclusion of this study is that women of childbearing age in conducting IVA tests are influenced by attitudes, cadre support and information sources. It is recommended that Puskesmas, especially health workers, be able to work closely with cadres and across sectors in developing cadres as an effort to support IVA health promotion so that the coverage of IVA tests in the area of ​​Puskesmas Sapat's technical support units can be carried out thoroughly.